Pentecostal doctrine in Apostles’ Creed and the 4IR: CFC and the River Church as case studies - Buti D. Mulutsi (African Journal of Pentecostal Studies)
Background: The 325 Nicene Apostles’ Creed was formulated to assist the church in knowing and practicing the correct belief as taught by the Apostles. The third article of Apostles’ Creed, I believe in the Holy Spirit, is significant to Pentecostal doctrine. The information as contained in the creeds dictates beliefs and practices to future generations. Transmission of that information is what led to movements such as Reformation and Pentecostalism. Because religion does not exist in isolation but is affected by geopolitical social statuses, Pentecostalism, similarly, benefited from geopolitical social statuses where it existed. Pentecostal movement benefited from industrial revolutions such as the use of steam, electricity and machinery. Cyberphysical technology is currently shaping the fourth industrial revolution (4IR).